1132. Integrated Quantitative Systems Pharmacology (QSP) Characterizing Viral Dynamics After Intramuscular (IM) Adintrevimab (ADI) Administration in Participants with Mild to Moderate Coronavirus Disease (COVID-19). (15th December 2022) - Tarbell, Evan; Van Wart, Scott A; Popejoy, Myra; Narayan, Kristin; Hershberger, Ellie; Pu, Xia; Gong, Jean; Rubino, Christopher M; Santulli, Andrew; Ambrose, Paul
Abstract: Background: ADI is a fully human IgG1 monoclonal antibody engineered to have an extended half-life with high potency and broad neutralization against SARS-CoV-2 and other SARS-like coronaviruses. The goal of our analysis was to develop a QSP model in which ADI concentrations in upper airway (UA) epithelial lining fluid (ELF) were linked to a viral dynamic model to describe the impact of ADI on SARS-CoV-2 viral load relative to placebo. Methods: The QSP model was fit in NONMEM Version 7.4 using PK data from a Phase 1 study (N=24, IV and IM) and from Phase 2/3 COVID-19 prevention (EVADE; N=659, IM) and treatment (STAMP; N=189, IM) studies. Saliva and NP samples were collected from STAMP study participants (pts) infected with the delta or omicron variants. The viral dynamic model was based on a published model and was modified to include both active (V) and deactivated (DV) virus (Fig). The viral dynamic model was fit to the NP swab viral load data (2 samples/pt) standardized to time since infection based upon recorded symptom onset. Saliva data (7-8 samples/pt) was fit sequentially using a biophase compartment given the peak viral load was modestly lower and peaked later than Day 1. Viral dynamic model (A) and simulated median (90% PI) NP viral load reduction in ADI-treated or placebo participants for delta (B) and omicron (C) variants Results: The QSP model provided an excellent fit to serum ADI concentration-time data after estimation of a transit rate to account for IM absorption, plasma volume, and the ADI-neonatal Fc receptor dissociation rate constant. The linked viral dynamic model captured the NP swab viral load data after estimating differences in within-host replication factor (R0 ) and viral production rate ( p ) by variant. Maximal ADI-induced effect (Smax ) on stimulating viral clearance ( c ) was fixed to 0.43 based upon prior modeling. ADI concentration in UA ELF resulting in 50% of S max (SC50 ) was estimated to be 0.086 for delta and 1.05 mg/L for omicron. Figure B and C show model-based simulated median (90% PI) viral load reduction in ADI-treated or placebo pts for delta and omicron variants. Conclusion: This QSP model, in conjunction with information on new variants available early in outbreaks (IC50, infectivity (R0 ), viral production rate [each a model parameter]), allows for rapid dose identification in response to emerging variants. Disclosures: Evan Tarbell, PhD, Adagio Therapeutics: Advisor/Consultant|Adagio Therapeutics: Grant/Research Support Scott A. Van Wart, PhD, Adagio Therapeutics: Advisor/Consultant|Adagio Therapeutics: Grant/Research Support Myra Popejoy, PharmD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Kristin Narayan, PhD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Ellie Hershberger, PharmD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Xia Pu, PhD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Jean Gong, PhD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Christopher M. Rubino, PharmD, Adagio Therapeutics: Grant/Research Support|Amplyx Pharmaceuticals, Inc: Grant/Research Support|AN2 Therapeutics: Grant/Research Support|Antabio SAS: Grant/Research Support|Arcutis Biotherapeutics, Inc: Grant/Research Support|B. Braun Medical Inc.: Grant/Research Support|Basilea Pharmaceutica: Grant/Research Support|Boston Pharmaceuticals: Grant/Research Support|Bravos Biosciences: Ownership Interest|Celdara Medical LLC: Grant/Research Support|Cidara Therapeutics Inc: Grant/Research Support|Cipla USA: Grant/Research Support|Crestone Inc: Grant/Research Support|CXC: Grant/Research Support|Debiopharm International SA: Grant/Research Support|Entasis Therapeutics: Grant/Research Support|Evopoint Biosciences Co.: Grant/Research Support|Fedora Pharmaceuticals: Grant/Research Support|GlaxoSmithKline: Grant/Research Support|Hoffmann-La Roche: Grant/Research Support|ICPD: Ownership Interest|ICPD Biosciences, LLC.: Ownership Interest|Insmed Inc.: Grant/Research Support|Iterum Therapeutics Limited: Grant/Research Support|Kaizen Bioscience, Co.: Grant/Research Support|KBP Biosciences USA: Grant/Research Support|Lassen Therapeutics: Grant/Research Support|Matinas Biopharma: Grant/Research Support|Meiji Seika Pharma Co., Ltd.: Grant/Research Support|Melinta Therapeutics: Grant/Research Support|Menarini Ricerche S.p.A: Grant/Research Support|Mutabilis: Grant/Research Support|Nabriva Therapeutics AG: Grant/Research Support|Novartis Pharmaceuticals Corp.: Grant/Research Support|Paratek Pharmaceuticals, Inc.: Grant/Research Support|PureTech Health: Grant/Research Support|Sfunga Therapeutics: Grant/Research Support|Spero Therapeutics, : Grant/Research Support|Suzhou Sinovent Pharmaceuticals Co.: Grant/Research Support|TauRx Therapeutics: Grant/Research Support|Tetraphase Pharmaceuticals: Grant/Research Support|tranScrip Partners: Grant/Research Support|Utility Therapeutics: Grant/Research Support|Valanbio Therapeutics, Inc.: Grant/Research Support|VenatoRx: Grant/Research Support|Wockhardt Bio AG: Grant/Research Support Andrew Santulli, BSE, Adagio Therapeutics: Advisor/Consultant|Adagio Therapeutics: Grant/Research Support Paul Ambrose, PharmD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds|Institute for Clinical Pharmacodynamics: President.